POLICY IMPLEMENTATION OF TRAVEL LICENSE RETRIBUTION RATES ON CITY TRANSPORT IN SUKABUMI CITY - Bella Rizka Khoerunisa; Andi Mulyadi; M Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2023)
Public transportation is a means provided for the community to facilitate their daily activities, including city transportation (angkot). In providing good service and easing the burden on the community, the Sukabumi City government issued a policy of abolishing route permit fees for city transportation. The purpose of this study is to find out how the implementation of route permit retribution tariff policies for city transportation in the city of Sukabumi. The research method used in this research is a qualitative approach, the research is descriptive in nature. Data collection techniques used by researchers are observation, interviews and documentation. This study uses four variables of policy implementation from George Edward. From the results of the study that policy implementation has been going well when viewed from the disposition and structure of the bureaucracy. However, in terms of communication and human resources, it has been implemented but not optimal. This can hinder the success in implementing route permit recommendations at the Sukabumi City Transportation Service and needs to receive more important attention from the government for the future in implementing route permit policies.